Stock market integration in Africa: Further evidence from an information‐theoretic framework. (23rd August 2022) - Nyakurukwa, Kingstone; Seetharam, Yudhvir
Abstract: This study revisits stock market integration in Africa using an information‐theoretic framework that quantifies the flow of information between exchanges. We use daily return data for seven MSCI‐classified African stock exchanges between 2011 and 2021. As Bitcoin has become an important asset class on the African continent, we also explore whether this cryptocurrency confers any diversification benefits. Our method holds that stock markets are integrated if there is a significant flow of information between exchanges. The results reveal a statistically insignificant flow of information among African stock exchanges, and for the few cases in which information flow is statistically significant, the magnitudes are low. South Africa is the most influential stock market, as it transmits most of the total transfer entropy (informational value) in the system. We also observe that African stock exchanges are weakly integrated with Bitcoin.